Coupling Genotyping and Computational Modeling in Prediction of Anti-epileptic Drugs that cause Stevens Johnson Syndrome and Toxic Epidermal Necrolysis for Carrier of HLA-B*15:02 - Lay Kek Teh; Manikandan Selvaraj; Zakaria Bannur; Mohd Ikhwan Mohd Ismail; Hanip Rafia; Wan Chung Law; Sapiah Sapuan; Santhi Puvanarajah; Pakeer Shaik Syed Ali; Mohd Zaki Salleh (Frontiers Media S.A., 2016)
Purpose. The importance of HLA-B*15:02 genotyping to avoid carbamazepine induced SJS/TEN and molecular modeling to predict the role of HLA-B*15:0 and AEDs induced SJS/TEN are investigated. Methods. DNA was extracted from eighty-six patients. The patients were genotyped by AS-PCR. Computational modeling of the HLA-B*15:02 followed by docking studies were performed to screen 26 AEDs that may induce ADR among HLA-B*15:02 carriers. Results. Odd ratio for CBZ induced SJS/TEN and HLA-B*15:02 was 609.0 (95% CI: 23-15873; p=0.0002). Molecular modeling studies showed that acetazolamide, ethosuxiamide, lamotrigine, oxcarbazepine, phenobarbital, phenytoin, primidone and sodium-valproate may induce ADR in HLA-B*15:02 carriers alike CBZ.  Conclusion. We confirmed HLA-B*15:02 as a predictor of SJS/TEN and recommend pre-screening. Computational prediction of DIHR is useful in personalized medicine.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.